Hubungan Burnout dengan Kinerja Perawat di Ruangan Rawat Inap - Lumbantoruan, Hanna Ceria; Nurhidayah, Rika Endah; Purba, Jenny Marlindawani (Journal of Telenursing (JOTING), 2024)
This study aims to analyze the relationship between burnout and nurse performance at Prof Dr. Hospital Chairuddin Panususnan Lubis USU. The Type of research used is Analytical survey method with cross-sectional approach is employed. The research sample amounted to 62 nurses on duty in the patient room using with total sampling. Data was collected using primary and secondary data and anlyzed using Chi- Square statistical test with a confidence level 0f 95%. The results showed that nurse burnout p=0,001. Conclusion, there is relathionship between burnout and nurse performance. Keywords: Burnout, Nurse performance